2015
DOI: 10.1007/s00234-015-1544-2
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution MRI using orbit surface coils for the evaluation of metastatic risk factors in 143 children with retinoblastoma

Abstract: High-resolution MRI is clinically valuable for the detection of metastatic, especially of advanced metastatic risk factors in children with retinoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
14
0
5
Order By: Relevance
“…By taking advantage of the good coil filling factor and non-isotropic sampling (e.g., thick slices), fine resolution images, approaching those in rodents, but in humans without sedation is possible using a cuedblinking procedure (Beenakker et al, 2013(Beenakker et al, , 2015Berkowitz et al, 2001;Berkowitz et al, 2013;Lindner et al, 2014;Sirin et al, 2015;Zhang et al, 2011). For example, we recently published human images collected at 58 mm axial resolution .…”
Section: Addressing Concerns About Memri and Mrimentioning
confidence: 97%
“…By taking advantage of the good coil filling factor and non-isotropic sampling (e.g., thick slices), fine resolution images, approaching those in rodents, but in humans without sedation is possible using a cuedblinking procedure (Beenakker et al, 2013(Beenakker et al, , 2015Berkowitz et al, 2001;Berkowitz et al, 2013;Lindner et al, 2014;Sirin et al, 2015;Zhang et al, 2011). For example, we recently published human images collected at 58 mm axial resolution .…”
Section: Addressing Concerns About Memri and Mrimentioning
confidence: 97%
“…Otherwise we would repeat imaging only if the patient develops changes concerning for an orbital lesion. While the sensitivity for detecting postlaminar disease is variable (50% in this study), it has been shown to improve with fat saturation [18] and surface coils [19], and MRI can reliably detect larger levels of invasion and orbital disease [20]. We found that in this very small cohort, there is no need to enucleate these patients if the intraocular disease can be controlled with therapy, and the nerve can be adequately and routinely imaged with B-scan ultrasound and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…While fundoscopy and optical coherence tomography can study the disc portion with high resolution, the remaining 3 portions are less accessible and require imaging studies, including MR imaging, sonography, and CT. 5,6 In fact, MR imaging is superior due to its high soft-tissue resolution, the absence of ionizing radiation, and its high diagnostic accuracy as demonstrated by several studies evaluating the sensitivity of MR imaging compared with histopathologic examination in the detection of tumor invasion. [7][8][9] According to Chawla et al 7 and Schueler et al, 8 the MR imaging sensitivity in detecting optic nerve abnormality is 60%-75%, while its specificity is up to 90%. Indeed, the optic nerve has been studied in healthy individuals and in pathologic states using MR imaging, CT, sonography, and cross-sectional anatomy.…”
mentioning
confidence: 99%